International Dictionary of Finance - Bannock, Graham and Manser,William (London Profile Books LTD, 2004)
"The International Dictionary of Finance provides succinct explanations of more than 2,000 terms used in today's global financial markets, including: Acid ratio and Adaptive expectations hypothesis, Backwardation and BIMBO, Call money and Convertible, Delta and Demurrage, Earn-out and Efficient markets hypothesis, Floater and Forward-forward, Gai atsu and Grey market, Harakiri swap and Hedge, Impact loan and In the money, Jahrgang and Jingen Index, Kerb trading and Kuponsteuer, Leaning into the wind and Liquidity trap, Maintenance period and Marking to market, Naked and Nomad, Open-mouth operations and Out of the money, Pass through and Payback, Quanto option and Quetzal, Rallonge and Ramp, Saturday-night special and SWIFT, Tap and Tick, Underwritten and Unsecured, Vertical spread and Vostro account, Wash sale and Window guidance, xd and Xetra, Yellow Book and Yield curve, and Zaitech and Zinssatz."--BOOK JACKET
Keywords: Finance -- Finance -- Dictionaries